ACCULTURATION OF TRADITIONAL AND ISLAMIC LAW IN THE PRACTICE OF INHERITANCE DISTRIBUTION OF THE MANDAILING TRIBE OF NORTH SUMATRA - Nur Saniah; Ahmad Bastomi (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
Acculturation of al-adat and Islamic law is a means to determine the extent to which Islamic law and local custom come into contact with the life practices of the Mandailing Tribe community of Islam without any contradictions. This research is empirical research with descriptive analysis. Research data were collected using observation and interview methods, then analyzed using content analysis methods. The results of this study indicate a synergism of the Mandailing tribal community, which adheres to a patrilineal kinship system to carry out Islamic law in parallel and local customs. The practice of sharing inheritance in the Mandailing tribal community is carried out traditionally by containing Islamic values. This practice is a realization of the philosophy of the Mandailing tribal community as